Antifungal activity of volatile and non-volatile metabolites of endophytes of Chloranthus elatior Sw. - Santra, Hiran Kanti; Banerjee, Debdulal (Frontiers in Plant Science, 2023)
Agriculture crops that have fungal infections suffer significant economic losses and reduced crop output. Chemical fungicides are used to tackle the problem, although this has additional detrimental side effects. There is an urgent need for safe and novel antifungals. Volatiles from plant-beneficial endophytic fungi are considered promising alternatives for the biological control of fungal pathogens as a sustainable approach in an agroecosystem. In the present investigation, a volatile-emitting sterile endophytic fungus, Diaporthe sp. CEL3 with bio-fumigation activity, was isolated from leaves of the ethnomedicinal plant Chloranthus elatior Sw., collected from the Passighat forest of North-East India. The camphor odor volatiles of CEL3 showed an inhibitory effect against eight fungal pathogens in vitro and minimized the infections of Monilinia fructicola, a causal agent of cherry fruit rot, in VOC-exposed cherry fruits. Rhizoctonia solani, Botrytis cinerea, Pythium ultimum, and M. fructicola were maximally inhibited up to 51.5%, 55.8%, 61.9%, and 78.5%, respectively, in comparison to control by the volatiles. Another isolate, CEL7, identified as Curvularia sp., synthesized non-volatile, soluble antifungal metabolites in its cell-free extracts and exhibited antifungal action. Bioassay-guided fractionation revealed the presence of imidazole compounds- (2-aminoethyl)-1H-imidazole-2-carbaldehyde, Pyrazole 4, 5 imidazole, 1-formyl 3-ethyl, phenol compounds-Phenol, 4-[2-(methylamino) ethyl]-, 6-Nitro-3-chlorophenol, Phenol, 2,4,6-tri-tert-butyl-, etc., in the cell-free extracts, with a MIC value of 250–2,000 µg ml−1. Optimum VOC emission was achieved in a modified PDA medium with instantly smashed potato (150 g L−1), dextrose (20 g L−1), wheat husk (20 g L−1), and yeast extract (20 g L−1), with additional salts. Interestingly, endophytic CEL3 emitted different types of volatiles, and trans-verbenol (32.25%), geraniol (30.32%), trans-ocimenol (12.90%), and mentha-4,8-diene (5.16%) were the prime ones. These VOCs cause lethal leakage of protein and necessary intracellular molecules from the fungal pathogens. Thus, CEL3 could potentially be used as a bio-fumigating agent to control post-harvest infections caused by fungal pathogens. This study opens a new approach to the use of endophytic fungi in biocontrol.